Bilateral Acute Lower Limb Ischemia Secondary to COVID-19. (February 2021) - Veerasuri, Sowmya; Kulkarni, Sachin R.; Wilson, William R.; Paravastu, Sharath C. V.
COVID-19 has to date affected over 5 million people worldwide and caused in excess of 300000 deaths. One of the principal finding is that of a thrombotic tendency within the lungs leading to high mortality. There have been increasing number of reports of peripheral arterial thrombosis as well. Most cases of arterial thrombosis is noted in patient in intensive care setting. Here-in we report a case of acute bilateral lower limb arterial thrombosis in a patient recovering at home with mild COVID-19 symptoms, highlighting that patients with milder symptoms may also suffer from prothrombotic state resulting in acute arterial occlusions. Arterial thrombosis should be suspected in these patients despite the absence of predisposing factors.